Clustering technical approaches of elite and world-class pole vaulters based on 10 years of measurement during competitions - Cassirame, J.; Eustache, E.; Sanchez, H.; Czingon, H.; Collet, P.; Homo, S.; Theodorou, A.; Panoutsakopoulos, V.; Bayne, H.; Frère, J. (Journal of Sports Sciences, 2024)
Recently, a variety of technical approaches in world-class pole-vaulters` behaviour have been observed. The aim of this study was to investigate the presence of subgroups using different technical approaches and to compare biomechanical performance differences. Biomechanical analysis of performances over 5.00 metres from 99 athletes were clustered with K-means methodology based on the relative position of the top hand at take-off and the direction of the top of the pole from take-off to the maximal pole bending. Analysis revealed four subgroups that were distinguished by higher and lower direction angle and relative position values. Despite differences in technique, the analysis did not reveal significant differences between these four groups in performance, take-off speed, or athlete anthropometrics. Nevertheless, these clusters showcased variations in pole-athlete interactions and pole bending, suggesting different strategies and physical requirements associated with each approach. Cluster 2 characterised the classical technique with a high direction angle and a take-off position close to the vertical plane. Cluster 4 displayed a technique with a low take-off angle, suggesting the influence of athletes like Lavillenie, in deviating from the conventional model. Understanding and categorising athletes based on their preferred technique can aid coaches in providing tailored instructions, leading to performance improvements.